A Study on the Development of Real-Time Chamber Contamination Diagnosis Sensors - Junyeob Lee; Kyongnam Kim (Sensors)
Plasma processes are critical for achieving precise device fabrication in semiconductor manufacturing. However, polymer accumulation during processes like plasma etching can cause chamber contamination, adversely affecting plasma characteristics and process stability. This study focused on developing a real-time sensor system for diagnosing chamber contamination by quantitatively monitoring polymer accumulation. A quartz crystal sensor integrated with flexible printed circuit boards was designed to measure the frequency shifts corresponding to polymer thickness changes. An impedance probe was also employed to monitor variations in the plasma discharge characteristics. The sensor demonstrated high reliability with a measurement scatter of 2.5% despite repeated plasma exposure. The experimental results revealed that polymer accumulation significantly influenced the plasma impedance, and this correlation was validated through real-time monitoring and scanning electron microscopy (SEM). The study further showed that the sensor could detect the transition point of the plasma state changes under varying process gas conditions, enabling the early detection of potential process anomalies. These findings suggest that the developed sensor system can be crucial for diagnosing plasma and chamber conditions, providing valuable data for optimizing preventive maintenance schedules. This advancement offers a pathway for improving process reliability and extending the operational lifetime of semiconductor manufacturing equipment.